2018
DOI: 10.1101/291435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Mitochondrial DNA Control Region might have useful Diagnostic and Prognostic Biomarkers for Thyroid Tumors

Abstract: Background: It is currently present in the literature that mitochondrial DNA (mtDNA)

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Recent study has indicated that mtDNA U haplogroup has more predisposition to benign and malign thyroid entities, and eight mtSNPs were shown to be associated with benign to malign thyroid tumor in Turkish population as well as they indicated that the D310 poly-C sequence might have a potential diagnostic biomarker for thyroid nodules (25). Therefore, these accumulated data with detected differences contribute to human population and evolutionary studies as well as giving valuable markers.…”
Section: A C a T G C T T A T G G T T A G Tmentioning
confidence: 92%
“…Recent study has indicated that mtDNA U haplogroup has more predisposition to benign and malign thyroid entities, and eight mtSNPs were shown to be associated with benign to malign thyroid tumor in Turkish population as well as they indicated that the D310 poly-C sequence might have a potential diagnostic biomarker for thyroid nodules (25). Therefore, these accumulated data with detected differences contribute to human population and evolutionary studies as well as giving valuable markers.…”
Section: A C a T G C T T A T G G T T A G Tmentioning
confidence: 92%